2019
DOI: 10.7874/jao.2019.00164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cochlear Implant Electrode Array Design on Electrophysiological and Psychophysical Measures: Lateral Wall versus Perimodiolar Types

Abstract: Background and Objectives The present study aims to investigate whether the cochlear implant electrode array design affects the electrophysiological and psychophysical measures. Subjects and Methods Eighty five ears were used as data in this retrospective study. They were divided into two groups by the electrode array design: lateral wall type (LW) and perimodiolar type (PM). The electrode site was divided into three regions (basal, medial, apical). The evoked compound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The mean values of standard deviation (STD) for threshold variations of the investigated electrodes during dendritic degeneration of each TN were 0.22 V for lateral electrode array and 0.07 V for perimodiolar array. Moreover, the perimodiolar array requires a lower threshold than the lateral electrode system in most cases, which is in line with findings in clinical studies (Cohen et al, 2001;Long et al, 2014;Lee et al, 2019).…”
Section: Extracellular Stimulationsupporting
confidence: 88%
See 2 more Smart Citations
“…The mean values of standard deviation (STD) for threshold variations of the investigated electrodes during dendritic degeneration of each TN were 0.22 V for lateral electrode array and 0.07 V for perimodiolar array. Moreover, the perimodiolar array requires a lower threshold than the lateral electrode system in most cases, which is in line with findings in clinical studies (Cohen et al, 2001;Long et al, 2014;Lee et al, 2019).…”
Section: Extracellular Stimulationsupporting
confidence: 88%
“…Techniques such as electrocochleography, polarity sensitivity, electrically evoked compound action potential (eCAP), and eCAP responses to changing interphase gap are used to evaluate the residual neural health (Santarelli et al, 2008;Garadat et al, 2012;Long et al, 2014;Pfingst et al, 2015;Hughes et al, 2018;Shearer et al, 2018;He et al, 2020). A recent study on lateral and perimodiolar CI systems reported a lower eCAP threshold in the apical region (Lee et al, 2019). Although their findings are in agreement with some studies (Cohen et al, 2001;Parkinson et al, 2002), others found the opposite result for the apical region (Polak et al, 2004;Brill et al, 2009;Van de Heyning et al, 2016).…”
Section: Degeneration Level Affects Cochlear Implant Outcomesmentioning
confidence: 70%
See 1 more Smart Citation
“…The perimodiolar type offers advantages over the lateral wall type in terms of lower stimulation levels, an expanded dynamic range, and better channel separation. Because perimodiolar configuration provides a placement of electrodes closer to spiral ganglions than the lateral wall, it leads to better neural stimulation, which may result in better speech perception [ 79 ]. Both lateral wall and perimodiolar electrode arrays can cause intra-cochlear trauma, but perimodiolar electrode arrays are likely to deviate to the scala vestibuli from the scala tympani more often than the lateral wall electrode arrays, leading to damage of the osseous spiral lamina/spiral ligament, which can induce new bone formation and ultimately impact the hearing quality [ 77 ].…”
Section: Electrode and Electrode Array Designmentioning
confidence: 99%
“…However, this option has potential disadvantages, including the increased likelihood of damage to cochlear structures as well as difficulty achieving complete electrode insertion (thus defeating the purpose of a longer electrode). Moreover, longer intracochlear electrodes are typically placed along the lateral wall of the scala tympani rather than in a perimodiolar position; the latter may be more desirable for reducing electrical charge levels, reducing spread of excitation, improving battery life, and producing adequate loudness (11,12). Even with the lateral wall design, the longest electrode on the market only reaches approximately 1.75 out of 2.5 turns into the cochlea, leaving approximately the upper (apical) third of the cochlea unstimulated (6).…”
mentioning
confidence: 99%